OPTIMIZATION OF PROCESS PARAMETERS FOR ENHANCING THE PROPERTIES OF BREADFRUIT SEED COAT-REINFORCED LOW-DENSITY POLYETHYLENE COMPOSITE - Okolie, Paul Chukwulozie; Nnaemeka, Ezenwa Obiora; Princewill Odeh, Calistus; Ndubuisi Okoye, Chibuzo; Augustine Uzodinma , Madumere; Nwachinemere, Chima Bright (Universitas Ngeri Malang, 2024)
This study investigates the optimization of process parameters to enhance the properties of breadfruit seed coat-reinforced low-density polyethylene composite ceiling boards. The research focused on assessing the effects of mixing ratio, press temperature, pressure, and press time on key material properties, including water absorption (WA), thermal conductivity (K), flexural strength (FS), and fire performance (FP). Breadfruit seed coats (BSCs) were treated with sodium hydroxide (NaOH) and acetic acid (CH₃COOH) to modify their surface properties before being mixed with kaolin (as a fire retardant) and low-density polyethylene (LDPE) to form composite boards through hydraulic pressing. The study also statistically analyzed and optimized the fabrication parameters using Response Surface Optimal Design (RSOD). The results demonstrated that kaolin content and mixing ratio significantly influenced WA, K, FS, and FP, while press temperature, pressure, and time had varying degrees of impact. The optimized parameters (20% mixing ratio, 180°C press temperature, 15 MPa press pressure, and 10 min press time) gave the optimal moisture resistance, thermal insulation, superior mechanical strength, and fire resistance. The findings highlight the potential of breadfruit seed coat composites as sustainable, cost-effective, and eco-friendly alternatives to conventional ceiling materials. This study contributes to agricultural waste recycling in composite manufacturing, promoting environmental sustainability while meeting modern construction demands